Supporting Newcomer English Learners During Remote Learning. (23rd February 2022) - Frantz, Laura; Protacio, Maria Selena
Abstract: In this article, the authors describe an English as a Second Language (ESL) teacher's attempt to provide more personalized support for her elementary English learners (ELs) during remote learning. The authors provide an in‐depth description of using voice recorders, a low‐tech and inexpensive device, to mitigate barriers and promote English development and literacy skills for ELs. They then describe the benefits of using this tool and provide ideas on how to extend the use of voice recorders for ELs during traditional instruction.